Facile Fabrication of CuO Nanoparticles Embedded in N-Doped Carbon Nanostructure for Electrochemical Sensing of Dopamine - Nebras Sobahi; Mohd Imran; Mohammad Ehtisham Khan; Akbar Mohammad; Md. Mottahir Alam; Taeho Yoon; Ibrahim M. Mehedi; Mohammad A. Hussain; Mohammed J. Abdulaal; Ahmad A. Jiman (Bioinorganic Chemistry and Applications)
In the present study, a highly selective and sensitive electrochemical sensing platform for the detection of dopamine was developed with CuO nanoparticles embedded in N-doped carbon nanostructure (CuO@NDC). The successfully fabricated nanostructures were characterized by standard instrumentation techniques. The fabricated CuO@NDC nanostructures were used for the development of dopamine electrochemical sensor. The reaction mechanism of a dopamine on the electrode surface is a three-electron three-proton process. The proposed sensor’s performance was shown to be superior to several recently reported investigations. Under optimized conditions, the linear equation for detecting dopamine by differential pulse voltammetry is Ipa (μA) = 0.07701 c (μM) − 0.1232 (R2 = 0.996), and the linear range is 5-75 μM. The limit of detection (LOD) and sensitivity were calculated as 0.868 μM and 421.1 μA/μM, respectively. The sensor has simple preparation, low cost, high sensitivity, good stability, and good reproducibility.